2002
DOI: 10.1183/09031936.02.01532001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lung volume reduction surgery in hamsters with elastase-induced emphysema

Abstract: Lung volume reduction surgery (LVRS) has been shown to improve respiratory mechanics in selected patients with severe emphysema. This is thought to be due to an improvement in lung elastic recoil. This study was aimed at gaining further understanding about the effects of LVRS on respiratory mechanics and airway function.Control hamsters instilled with saline (Ctrl; n=8) were compared with emphysematous animals that underwent either a sham operation (Sham; n=7) or an LVRS (LVRS; n=7).As expected, there was a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…This proved to be a better predictor of the effect than the increase in lung elastic recoil, confirming the reasoning developed above and the theoretical model of FESSLER and PERMUTT [83]. This model was also confirmed in a recent animal model [86].…”
Section: Potential Benefitssupporting
confidence: 82%
See 1 more Smart Citation
“…This proved to be a better predictor of the effect than the increase in lung elastic recoil, confirming the reasoning developed above and the theoretical model of FESSLER and PERMUTT [83]. This model was also confirmed in a recent animal model [86].…”
Section: Potential Benefitssupporting
confidence: 82%
“…The hypotheses explaining the improvement include: improved lung mechanics, increased lung elastic recoil [80,81], reduced intrinsic positive inspiratory pressure [82], reduced hyperinflation, increased respiratory muscle strength due to geometric factors [74][75][76][77][78], improved ventilation/perfusion matching, and reduced pulmonary vascular resistance. There is evidence that the major mode of action is resizing of the lungs [83][84][85][86]. This means that, in emphysema, lung mechanics deteriorate because the lung is disproportionately expanded compared to the chest wall.…”
Section: Potential Benefitsmentioning
confidence: 99%
“…The increase in lung volume observed in hamsters was within the range reported in the literature for a single dose model in this species (12,20,26,27,32,35,45), whereas in rats, the increase in lung volume after three doses of elastase was significantly smaller than in hamsters and not different from values reported in this species after a single dose (10,17,18,20). Thus, species differences in the magnitude of histological and functional changes after elastase treatment suggest the existence of protective mechanisms in the rat lung that contribute to the prevention of severe emphysema development.…”
Section: Discussionsupporting
confidence: 84%
“…Species differences in susceptibility to elastase were suggested by a study done in our laboratory, showing that Sprague-Dawley rats develop only mild emphysema (3) with the dose of elastase known to produce severe panlobular emphysema in hamsters (20,42,43). Prompted by these findings, we performed a literature search on the increment in lung volume reported in rats and hamsters after treatment with IT elastase and found that, for the same dose of elastase per kilogram body weight, lung volume enhancement is of the order of 200 -300% in hamsters (12,20,26,27,32,35,45) and only of 35% in rats (10,17,18,20).Species differences in susceptibility to elastase are likely to be multifactorial and are related to many independent factors specific to each one of them. However, given the specificity of ␣1-AT for the instilled elastase (24), we hypothesized that the development of severe emphysema is prevented in rats by the high serum level of ␣1-AT reported in this species compared with hamsters (19).…”
mentioning
confidence: 98%
“…Chronic obstructive pulmonary disease (COPD), specifically emphysema, is a highly relevant disorder that inducts respiratory muscle dysfunction mainly due to overinflated lungs [18][19][20]. Currently, there is no cure for this disorder.…”
Section: Introductionmentioning
confidence: 99%